Sosialisasi Literasi Media Secara Mindfullness Di SMPN 2 Kota Bandar Lampung - Bangun Suharti (CV. Multi Kreasi Media, 2024)
The utilization of media and social media (digital media) among teenagers should ideally be used mindfully. Mindfulness in utilizing the media means using the media wisely, being alert to the potential impacts caused by addiction and considering ethics because digital media content is widely spread in public spaces. This is because media content can be consumed by the public at large, so the impact can also be widespread. PKM activities are carried out through this socialization activity on the importance of digital media literacy at SMPN 2 in Bandar Lampung city. The provision of material is carried out through counseling activities, continuing with dialogue and exercises in preparing independent programs to make self-regulation in utilizing digital media. The purpose of this PKM activity is so that students of SMPN 2 Bandar Lampung city can utilize digital media more wisely and be able to make self-regulation in order to prevent addictive (addiction) to the use of digital media (social media). The conclusion of this PKM activity, has been able to increase the understanding and ability of media mindfulness so that students can develop self-regulation and self-protection programs in the media.